Australian adolescents' beliefs and help-seeking intentions towards peers experiencing symptoms of depression and alcohol misuse - D. I. Lubman; A. Cheetham; A. F. Jorm; B. J. Berridge; C. Wilson; F. Blee; L. Mckay-Brown; N. Allen; J. Proimos (BMC, 2017)
Abstract Background Many young people are reluctant to seek professional help for mental health problems, preferring to rely on their friends for support. It is therefore important to ensure that adolescents can identify signs of psychological distress in their peers, talk to them about these, and help them access appropriate services when necessary. The current study examined adolescents' ability to recognise symptoms of depression and alcohol misuse, perceived barriers to help-seeking, and their intentions to encourage a peer to seek help from a range of informal and formal help sources. Method The current study used baseline data from a randomised controlled trial of a school-based intervention that teaches adolescents how to overcome barriers to accessing professional help for mental health and substance use problems (MAKINGtheLINK). Participants (n = 2456) were presented with two vignettes portraying depression and alcohol misuse, respectively, and were asked to identify the problems described. Participants provided data on their past help-seeking behaviour, confidence to help a peer, perceived barriers to help-seeking, and intentions to encourage a peer to seek help. Results Health professionals were the main source of help that participants had relied on for depressive symptoms, followed by friends and parents. In contrast, friends were the main source of help that participants had relied on for alcohol and other drug problems, followed by health professionals and parents. Just over half of the sample correctly identified the problems described in the two vignettes, although the majority of participants were confident that they could talk to a peer and help them seek professional help if needed. Most agreed that the vignettes described problems that warranted professional help, however approximately half the sample was unsure or considered it unlikely that they would seek help if they experienced similar problems. For both disorders, participants were most likely to encourage a peer to seek help from their family, followed by formal help sources and friends. Conclusions While the results point towards a greater willingness to approach formal help sources, particularly for depression, peers remain an important source of support for young people experiencing mental health and substance use problems.